Penilaian Implementasi GDFP (Good Diary Farming Practice) Pada Peternakan Rakyat Di Kecamatan Ngancar, Kabupaten Kediri, Jawa Timur - Muarifah, Hanum; Winarti, Atik; Arifin, Ikhsan Abimanyu (CV. SINAR HOWUHOWU, 2024)
Good dairy farming practice is a guideline used by smallholder farmers and companies in carrying out good dairy farming agribusiness and meeting standards so that cow productivity is maintained and milk is protected from health threats. This research took place in Ngancar District, Kediri Regency with 30 dairy farmers as respondents. The survey method is the method used in this research by collecting data using questionnaires, interviews and direct observation in the cage. The questionnaire contains questions from six aspects, namely livestock health, milking hygiene, nutrition, livestock welfare, environment and socio-economic management. The grouping of breeders based on livestock ownership is divided into 3 strata. Data analysis in this research is descriptive with a comparison of quantitative and qualitative aspects of GDFP. The results of the assessment of GDFP implementation in Ngancar District in the three breeder strata received good scores (3.28; 3.32; and 3.44). The implementation of GDFP has a high value in all strata in the milking hygiene aspect and a low value in the socio-economic management aspect of strata 1 (2.84). Increased attention to aspects of socio-economic management on smallholder farms is expected to contribute to increased implementation of GDFP